PARTISIPASI PEREMPUAN DALAM PERUMUSAN KEBIJAKAN PEMBANGUNAN EKONOMI DI KELEMBAGAAN DAERAH KABUPATEN LAMPUNG TENGAH - Herlintati - (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2013)
Regional economic development is a change for the better, the economy that includes theestablishment of new institutions, the development of alternative industries, improving the capacity ofthe existing workforce to produce products and services better, identifying new markets, transfer ofknowledge knowledge and development of new businesses in order to improve the economic andsocial welfare.The results showed that the capacity and participation of women in leadership positions whodetermine the policy / decision-economic development plans in the region is still relatively weakinstitutions, lack of access to women's involvement in the formulation of the program due to thecomposition of factors on the structural position of women in institutions, lack of knowledge,experience and capabilities of women in the formulation of program access, program establishmentand implementation of economic development programs at the institutional center of Lampungregency.Ability and women's participation in responding to proposals from the community ineconomic development in the institutional area in Lampung regency was still relatively limited. abilityin response to the proposed program and budget of the subordinate financing in economicdevelopment is still relatively weak institutions. The low composition on the structural position ofwomen in local institutions turned out to limit the access capability, authority and power of women toinfluence decisions in the formulation of the proposed policy. Women's ability to defend and fight forthe proposed program is still weak or not yet optimal. Based on these results concluded thatwomen's participation in the formulation of economic policy in the institutional area of Lampungregency was still low.